Binder-free three-dimensional high energy density electrodes for ionic-liquid supercapacitors1. Issue 72 (18th September 2015) - Tran, Chau; Lawrence, Daniel; Richey, Francis W.; Dillard, Caitlin; Elabd, Yossef A.; Kalra, Vibha
<x xml:space="preserve">Abstract</x> We demonstrate a facile methodology to fabricate binder-free porous carbon nanofiber electrodes for room temperature ionic-liquid supercapacitors.